Analysis of Coordinated Pricing Model of Closed-Loop Supplying Chain Based on Game Theory in E-Commerce Environment. (9th April 2022) - Zhou, Zhaoquan; Gu, Bin
Abstract : Although the research of closed-loop supply chains has attracted great attention and some research results have appeared, it has not formed a complete theoretical system. People have studied many pricing and coordination models by modeling the closed-loop supply chain system, but most of these models are based on the research under the conditions of market demand determination and information symmetry, which is far from the practice of the operation of the closed-loop supply chain system, so it is difficult for these studies to improve its theoretical guidance ability. Starting from reality, this paper fully considers various situations closer to reality, such as multichannel recycling, a conflict between sales channels and recycling channels, and double trust in a complex practical environment. This paper constructs the corresponding pricing decision-making model for analysis and research and further discusses the coordination and incentive mechanism of each node enterprise in the closed-loop supply chain system, so as to realize the overall optimization of the closed-loop supply chain. In this paper, the pricing strategy of the closed-loop supply chain and the coordination of interests among participants are studied by using game theory under the practical e-commerce model. Firstly, the traditional sales channel is considered, and the different situations of centralized decision-making and decentralized decision-making are compared. In short, cooperation can increase profits and achieve win-win results. Finally, this paper puts forward some methods of construction coordination of closed-loop supply chain to guide the closed-loop supply chain to reduce costs, improve competitive advantage, and make the development of closed-loop supply chain more practical significance.